Analysis of Solar Radiation Against Solar Panel 50 WP - Muhammad Irwanto; Poltak Sihombing; Faisal Irsan Pasaribu (Journal of Electronics, Telecommunication, Electrical, and Physics Science, 2022)
Solar cell technology is a technology that converts solar energy into electrical energy. This study discusses the radiation of polycrystalline solar cells with a maximum output power of 50 WP. The aim of this study was to determine the effect of light intensity on the yield of electrical energy. The research method is measuring the intensity of the sun using a lux meter and electric current generated from solar panels. From the results of measuring the intensity of the sun for 4 weeks using a 50 Wp cell at 08.00 WIB the average weather is sunny. At 08.00 WIB, the intensity of the sun is 398.05 Wp/m, the voltage is 16.45 volts and the current is 0.73 amperes. The brighter the sun and as long as it is not covered by clouds, the increase in the intensity of the sun at its peak at 14.00 WIB has an intensity of 540.18 W/m, the voltage value is 18.425 Volts and the current value is 0.81 Ampere. The change in value is getting smaller at 17.00 WIB the intensity is 384.75 W/m and for the voltage is 15.7 V and the current is 0.59 A. This is because at that time the average weather was very sunny, and the sun was not covered by clouds.